Locusts an on-going battle - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
This year, the sum of 33 million US dollars was spent in fighting locusts in the Sahel. Unfortunately, this did not lead to the elimination of this plague. Some factors, like the use of insecticides and a relatively long rainy season, have...